Videoassistance treatment of rectum ﬁ stulas: the experience and treatment results - P. V. Tsygankov; V. S. Groshilin; M. I. Sultanmuradov; G. A. Mrykhin; E. V. Zhinzhilo (Медицинский вестник Юга России, 2018)
Objective: Evaluation of the eff ectiveness and identifi cation of the benefi ts of a video-assisted fi stula treatment method using fi stuloscopy, in comparison with traditional methods of surgical treatment of complex forms of chronic paraproctitis, trans- and extrasphincteric, relapsing rectal fi stulas. Materials and methods: A complex analysis of the results of surgical treatment was carried out in 228 patients with chronic paraproctitis, transphincteric, ectrasphincteric, including recurrent rectal fi stulas, divided into three groups (main and two control), depending on the surgical methods of chronic paraproctitis used. Results: the result of surgical treatment of pararectal fi stulas in the three study groups was compared. Th e eff ectiveness of treatment was assessed by the results of immediate and long-term postoperative period. It has been established that the use of a video-assisted fi stula treatment method using fi stuloscopy excludes the presence of an extensive postoperative wound in the perianal region, which signifi cantly reduces the likelihood of its secondary infection, and the sphincter trauma, and in fact virtually eliminates its insuffi ciency. Th e use of video-assisted method of treatment of fi stulas made it possible to reduce the number of postoperative complications. Conclusions. Th e fi nal results (92.7% of favorable outcomes) allow us to recommend a video-assisted treatment for fi stulas for wide practical implementation.